ASPECTS OF THE INFLUENCE ASSESSMENT OF THE NEW CONSTRUCTION DURING THE RECONSTRUCTION OF URBAN TERRITORY AREAS IN THE DENSE BUILDING CONDITIONS - Prusov, Dmitry (Proceedings of National Aviation University, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]-->The scientific substantiation concept has been considered for the urban development and territorial planning reconstruction principles of the urban area sections with dense building and difficult engineering-geological conditions for scientific and technical support of all reconstruction processes and recommendations elaboration for a safe and balanced development of built-up territories and more efficient use of housing estates in the present social and economic conditions.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->